A New Way to Identify Thin Sheet Behaviour: Micro-In Def - Pierrick Malecot Malecot; Gemala Hapsari; Sebastien Thibaud; Fabrice Richard (International Journal of Quantitative Research and Modeling, 2020)
Incremental forming is a rapid prototyping process which uses a forming tool toform a sheet metal according to a predetermined trajectory. In this work, a micro incremental deformation test (Micro InDef test) derived from the principle of single point incremental sheet forming is developed and proposed. A complex mechanical loading is applied and has a strong potential for the identication of inelastic behavior using inverse method. In the rst part, this work addresses the parameters identication and validation procedures of ductile damage behavior of ultra-thin sheet metal under very large strain during this instrumented Micro InDef test. An inverse nite element method based on the comparison between numerical and experimental axial forming forces of the micro incremental deformation test is employed to extract a coupled ductile damaged plastic model. In the second part, the objective is to prove the reliability of ductile damage parameters identication using forming force. The richness of data contained in forming force is quantied and compared to the one from tensile test. Firstly, the verication of the estimated parameter's reliability is done via a simple analysis based on the forming force sensitivity to material parameters and secondly by calculating elastoplastic and elastoplastic with ductile damage.